The Fabp5/calnexin complex is a prerequisite for sensitization of mice to experimental autoimmune encephalomyelitis. Issue 12 (30th October 2020) - Paskevicius, Tautvydas; Jung, Joanna; Pujol, Myriam; Eggleton, Paul; Qin, Wenying; Robinson, Alison; Gutowski, Nick; Holley, Janet; Smallwood, Miranda; Newcombe, Jia; Zochodne, Douglas; Chen, Xing‐Zhen; et al.
Abstract: We previously showed that calnexin (Canx)‐deficient mice are desensitized to experimental autoimmune encephalomyelitis (EAE) induction, a model that is frequently used to study inflammatory demyelinating diseases, due to increased resistance of the blood‐brain barrier to immune cell transmigration. We also discovered that Fabp5, an abundant cytoplasmic lipid‐binding protein found in brain endothelial cells, makes protein‐protein contact with the cytoplasmic C‐tail domain of Canx. Remarkably, both Canx‐deficient and Fabp5‐deficient mice commonly manifest resistance to EAE induction. Here, we evaluated the importance of Fabp5/Canx interactions on EAE pathogenesis and on the patency of a model blood‐brain barrier to T‐cell transcellular migration. The results demonstrate that formation of a complex comprised of Fabp5 and the C‐tail domain of Canx dictates the permeability of the model blood‐brain barrier to immune cells and is also a prerequisite for EAE pathogenesis.